2020
DOI: 10.1186/s42836-020-00041-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intravenous iron monotherapy for patients with iron deficient anemia undergoing total knee arthroplasty

Abstract: Background Unnecessary costs and complications can be reduced by increasing hemoglobin (Hb) levels and minimizing blood transfusions in patients who underwent total knee arthroplasty (TKA). This study aimed to determine the effects of intravenous iron monotherapy before TKA on preoperative iron deficient anemia and postoperative transfusion rates. Methods This prospective cohort study included 45 patients scheduled for TKA in the experimental group (Group I) and 221 patients who underwent TKA in 2015 and 2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…15 This is a concept that has been widely used in other departments and has recently been used in the field of orthopaedics after major surgeries, such as arthroplasty. 8,16,17 Our results concurred with the findings of other Postoperative IV Iron Supplementation Increases Hemoglobin Level in TKA Nam et al…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…15 This is a concept that has been widely used in other departments and has recently been used in the field of orthopaedics after major surgeries, such as arthroplasty. 8,16,17 Our results concurred with the findings of other Postoperative IV Iron Supplementation Increases Hemoglobin Level in TKA Nam et al…”
Section: Discussionsupporting
confidence: 91%
“…15 This is a concept that has been widely used in other departments and has recently been used in the field of orthopaedics after major surgeries, such as arthroplasty. 8,16,17 Our results concurred with the findings of other studies wherein iron supplementation decreased hemoglobin drops at 2 to 6 weeks after TKA surgery. 8,13,18,19 Our study showed that the hemoglobin drop of the I group during hospitalization was lower than the NI group after administration of iron supplementation, even though the difference did not reach statistical significance.…”
Section: Discussionsupporting
confidence: 91%
“…In total, 13 studies met our inclusion criteria. The eligible 13 studies comprised five RCTs [ 21 25 ] and eight observational studies: two prospective [ 26 , 27 ], five retrospective cohort studies [ 28 32 ], and one observational study [ 33 ] comparing a prospective intervention group to a historic cohort. Table 2 gives an overview of the study characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…of studies, n (%) No. of studies reporting as primary outcome Variation in reported outcome Death Mortality/survival Mortality 5 (38) [ 21 , 25 27 , 30 ] 0/5 - Reported as number or percentage of patients deceased - Time points: from up to 30 days to 6 months after intervention Physiological/clinical outcomes Blood and lymphatic system outcomes Hemoglobin (Hb) levels 12 (92) [ 21 27 , 29 – 33 ] 6/12 - Continuous variable: reported as mean ± SD concentrations or differences in concentrations - Categorical variable: success versus failure in reaching target Hb (10g/dL); number/percentage of patients reaching Hb >10g/dL - Time points: at baseline, 28-35 days prior to surgery, at day of surgery, 1 day to 6 months postoperatively, at discharge - 2 studies reported number of patients reaching a Hb level of 10 g/dL before surgery and time needed for it Change in iron metabolism parameters 6 (46) [ 21 , 22 , 24 , 25 , 30 ] 1/6 - Reported as mean ± SD concentrations or differences in concentrations of iron parameters: ferritin, transferrin, transferrin saturation, iron, iron-binding capacity - Time points: up to 4 preoperatively and up to 4 postoperatively or not specified Blood loss 2 (15) [ 24 , 33 ] 0/2 - Reported as estimated mean blood loss ± SD and blood loss in drainage - Time points: 5 and 7 days postoperatively Other outcomes regarding hematopoiesis 2 (15) [ 22 , 29 ] 0/2 - Reported as mean ± SD or differences in number of white and red blood cells, and mean cell volume - Time points: preoperatively up to 4 weeks and up to 4 weeks postoperatively Adverse events Adverse events (AE) See variation in reported outcome 10 (77) [ 21 ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation